Optimation of Production Input in White Shrimp (Litopenaeus vannamei) Culture: A Case Study in UD. Jasa Hasil Diri at Desa Lamaran Tarung, Kecamatan Cantigi, Kabupaten Indramayu - Diatin, I.; Arifianty, S.; Farmayanti, N. (Indonesian Society of Scientific Aquaculture (ISSA), 2008)
UD Jasa Hasil Diri (UD JHD) is a company in Indramayu which culture the white shrimp. UD JHD started this culture in 2003, and now UD JHD's dam out area has reach 26 ha. Total production of white shrimp in 2006 was 125,854.5 kg. The production cost of white shrimp culture that must be spending by UD JHD reached IDR 2,842,427,294. This production cost was allocated to get all variable input such as: seed, food, calcium, fertilizer, vitamin, probiotic, medicine, labor, diesel fuel, and gasoline. The used of production input already in optimum condition. Based on the result of linear study for seed used was optimum at 7,830,667 tails, foods at 204,387.7 kg, calcium at 25,170.9 kg, fertilizer at 503.4 kg, vitamins at 75.5 kg, probiotic at 683.4 kg, medicines at 4,279.1 kg, harvests at 1,258.5 hours, diesel fuel at 104,459.2 liters, and gasoline at 1,200 liters. The cost of production input based on linear study was IDR 2,403,220,000. Thus, UD JHD could reduce this cost by IDR 439,207,294 to get 125,854.5 kg shrimps. Keywords: optimum, production input, cost, white shrimp ABSTRAK UD Jasa Hasil Diri (UD JHD) merupakan sebuah perusahan yang membudidayakan udang vaname di Indramayu. Perusahaan ini memulai usahanya sejak tahun 2003, dan saat ini memiliki tambak seluas 26 ha. Total produksi udang vaname pada tahun 2006 adalah 125.854,5 kg. Biaya yang harus dikelurkan oleh UD JHD untuk memproduksi budidaya udang vaname mencapai Rp. 2.842.427.294. Biaya produksi ini dialokasikan untuk memperoleh berbagai input produksi seperti benur, pakan, kalsium, pupuk, vitamin, probiotik, obat-obatan, tenaga kerja, solar dan bensin. Penggunaan input produksi telah mencapai kondisi optimum. Berdasarkan hasil uji linier, kondisi optimum untuk benih yang ditebar adalah 7.830.667 ekor, pakan sebanyak 204.387,7 kg, kalsium 25.170,9 kg, pupuk 503,4 kg, vitamin 75,5 kg, probiotik 683,4 kg, obat-obatan 4.279,1 kg, masa pemeliharaan 1.258,5 jam, solar 104.459,2 liter, and bensin 1.200 liter. Berdasarkan analisis linier, biaya input produksi adalah Rp. 2.403.220.000. Dengan demikian, UD JHD dapat menurunkan biaya menjadi Rp. 439,207,294 untuk memperoleh 125.854,5 kg udang vaname. Kata kunci: optimum, input produksi, biaya , udang vaname